Geographical distribution of museums in Iraq - Rashk, Safaa; Muhamad , Nahdh (Al-Adab Journal, 2025)
The research aims to study the geographical distribution of museums throughout Iraq, with the exception of the Kurdistan region, with the help of modern geographic information systems technology, and since Iraq is one of the countries rich in archaeological sites, an ancient and prosperous civilization appeared on its land whose ruins still exist to this day, which is the raw material from which It has tourism This led to the establishment of many museums throughout Iraq, but their investment was not at the required level at the internal and external levels. Therefore, interest in museums and their optimal tourism investment will lead to achieving development of tourist areas and their regional surroundings in particular and to advancing the national economy in general. The number of museums reached more than (34), varying in their geographical distribution among the Iraqi governorates, as the highest percentage was concentrated in Baghdad Governorate, while the rest of the governorates obtained lower percentages of this distribution.